2022
DOI: 10.3390/molecules27175595
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genomic Study of Inhibin Molecule Production through Granulosa Cell Gene Expression in Inhibin-Deficient Mice

Abstract: Inhibin is a molecule that belongs to peptide hormones and is excreted through pituitary gonadotropins stimulation action on the granulosa cells of the ovaries. However, the differential regulation of inhibin and follicle-stimulating hormone (FSH) on granulosa cell tumor growth in mice inhibin-deficient females is not yet well understood. The objective of this study was to evaluate the role of inhibin and FSH on the granulosa cells of ovarian follicles at the premature antral stage. This study stimulated immat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Talpur et al . [ 21 ] demonstrated, using a weighted Gene Co-Expression Network Analysis (WGCNA) algorithm that relevant modules and key gene drivers associated with external traits can be determined, further identifying differentially expressed genes (DEGs). Integrating transcriptomics and metabolomics data allows for normalization and statistical analyses across different biomolecular levels, facilitating the exploration of molecular relationships between these levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Talpur et al . [ 21 ] demonstrated, using a weighted Gene Co-Expression Network Analysis (WGCNA) algorithm that relevant modules and key gene drivers associated with external traits can be determined, further identifying differentially expressed genes (DEGs). Integrating transcriptomics and metabolomics data allows for normalization and statistical analyses across different biomolecular levels, facilitating the exploration of molecular relationships between these levels.…”
Section: Introductionmentioning
confidence: 99%
“…Farmanullah et al [20] used advanced bioinformatics methods such as hierarchical clustering, enrichment analysis, active site prediction, and functional domain identification through transcriptomics to analyze important genes that could be used as biomarkers and therapeutic targets for mastitis. Talpur et al [21] demonstrated, using a weighted Gene Co-Expression Network Analysis (WGCNA) algorithm that relevant modules and key gene drivers associated with external traits can be determined, further identifying differentially expressed genes (DEGs). Integrating transcriptomics and metabolomics data allows for normalization and statistical analyses across different biomolecular levels, facilitating the exploration of molecular relationships between these levels.…”
Section: Introductionmentioning
confidence: 99%